Optimalisasi Produksi: Berkelanjutan, Efisien, dan Ramah Lingkungan dengan Penerapan Total Productive Maintenance (TPM) menuju Era Green Building (Studi Kasus: Perusahaan Daur Ulang Plastik PT XYZ) - Mohammad Shodiq Wahyu Riamto; Rusindiyanto Rusindiyanto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
The industrial revolution today is not only oriented towards quality results and cutting-edge technology such as the industrial revolution 4.0. Today's industry is developing by implementing the concept of green building or green industry. Green industry is a concept and idea that an industry no longer only takes into account the advantages and benefits for its company, but also needs to pay attention to the level of efficient use of natural resources and energy sources and minimize the impact of the production process which is felt by the surrounding community and has a negative impact on the environment. , PT XYZ is one of the companies engaged in integrated plastic recycling in the world which processes plastic waste into quality and environmentally friendly products. In order to move towards a green building era that applies efficiency and effectiveness standards for a work system, PT XYZ will plan to determine the effectiveness value of a sustainable production line using the Total Productive Maintenance (TPM) theory. To measure the effectiveness value of a sustainable production process in TPM, the OLE (Overall Line Effectiveness) measurement method can be used. OLE is a tool for measuring the effectiveness of the production process, a modification of the OEE tool which is specifically for determining the value of process effectiveness in sustainable production. From the TPM measurement results, a production line effectiveness value using the OLE method was obtained of 91.7% during September 2023.